Study on Driver Gaze Characteristics in Sight Distance Limited Section of Mountain Highway Based on Visual Information. (6th January 2022) - Tang, Yuzhou; Peng, Xiaodang; Xu, Shiyong; Bai, Mingju; Lin, Lifang; Sun, Haihan
Abstract : In order to study the gaze behavior characteristics of drivers in mountainous road sections with limited sight distance, the real vehicle test is carried out by using Smart Eye Pro 5.7 noninvasive eye tracker. Combined with the sight distance change rate theory, 6 typical test representative mountainous sections are selected to study the gaze distribution law and gaze duration of drivers in different mountainous sections. The research shows that when the driver drives on the test section with the most unfavorable sight distance of 44 m, 50 m, and 56 m, the fixation characteristics of "from far to near" are significant, and the long fixation duration accounts for a large proportion of the driver. When the driver drives on the section with the most unfavorable sight distance of more than 70 m, i.e., the sight distance change rate of less than 1.33, the fixation characteristics of "from far to near" disappear. The driver's fixation stability increases, the fixation freedom increases, and the proportion of medium and long fixation duration decreases. The data analysis provides a theoretical basis for drivers to pass safely in mountainous sections.